Multi-Parametric Field Experiment Links Explosive Activity and Persistent Degassing at Stromboli - Thivet, Simon; Harris, Andrew J. L.; Gurioli, Lucia; Bani, Philipson; Barnie, Talfan; Bombrun, Maxime; Marchetti, Emanuele (Frontiers in Earth Science, 2021)
A multi-parametric experiment at Stromboli volcano (Aeolian Islands, Italy) was installed in July 2016 focusing on the normal explosive activity and persistent degassing. A FLIR thermal camera, an UV SO₂ camera and a scanning DOAS, were deployed to record pyroclast and SO2 masses emitted during individual explosions, as well as persistent SO₂ fluxes, respectively. An ASHER instrument was also deployed in order to collect ash fallouts and to measure the grain size distribution of the samples. SO2 measurements confirm that persistent degassing was far greater than that emitted during the explosions. Further, we found that the data could be characterized by two periods. In the first period (25-27 July), activity was mainly characterized by gas-dominated (type 0) explosions, characterized by high velocity jets. Pyroclast mass fluxes were relatively low (280 kg/event on average), while persistent SO2 fluxes were high (274 t/d on average). In the second period (29-30 July), activity was mainly characterized by particle-loaded (type 1) explosions, characterized by velocity jets. Pyroclast mass fluxes were almost ten times higher (2400 kg/event on average), while persistent gas fluxes were significantly lower (82 t/d on average). Ash characterization also indicates that type 0 explosions fragments were characterized by a larger proportion of non-juvenile material compared to type 1 explosions fragments. These data suggest that Stromboli’s type 1 explosions can be associated with low levels of degassing and the mass of particles accompanying such explosive events depends on the volume of a degassed magma cap sitting at the head of the magma column. This could make the classic particle-loaded explosions of Stromboli an aside from the true eruptive state of the volcano. Instead, gas-dominated explosions can be associated with high levels of degassing and are indicative of a highly-charged (with gas) system. We thus suggest that relatively deep magmatic processes, such as persistent degassing and slug formation can rapidly influence the superficial behavior of the eruptive conduit, modulating the presence or absence of degassed magma at the explosion/fragmentation level.